Pelaksanaan Kegiatan Pengajaran Literasi Numerasi untuk Kelas 5 SD di SDN Japanan I dan II - Ramadhani Mahendra K; Devianra Luthfi A; Fitri Auliya R; Dimas Tri P; Savira Vagantree V; Zahra Fadilla (Universitas 45 Surabaya, 2024)
SDGs is a form of global and national commitment to develop public prosperity. Student Community Service is one of the methods to increase SDGs score. Direct participation in teaching is a work program to achive that goal. Teaching is carried out by devevloping teaching materials and then taught to the fifth grade student of SDN Japanan I and II. Teaching materials is built by considering curriculum module for the national assessment. PISA indicator indicate that student level of understanding is on the third level, meaning student can interprate and do the simple problem. Student ability to literate and numerate need more habituation towards many program to ensure the increase of student’s critical, creative, and innovative thinking.